Molecular Pathology of Liver Diseases - Monga, Satdarshan P. S.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2011)
Molecular Pathology of Liver Diseases integrates the traditional knowledge of physiological and pathological processes in the liver with a balanced emphasis on fundamental concepts; timely advances in cellular and molecular mechanisms; and applied pathology. The textbook is organized into several sections, each of which includes an array of chapters that progressively and cohesively elaborate on pertinent liver biology and pathology. The first three sections discuss the cellular composition of the liver along with their specialized functions, and further dissect the molecular basis of the cellular processes that are so unique to the liver. The next section examines the mechanisms that are commonly implicated in the cellular and molecular basis of several hepatic pathologies, followed eventually by a section each on a multitude of non-neoplastic and neoplastic diseases of the liver. Molecular Pathology of Liver Diseases is a comprehensive reference on liver pathobiology for basic, translational and clinical researchers and physicians The format of the volume will serve as a ready reference to relevant topics in the liver, thus providing a practical disease-based integrative resource on the molecular pathology of liver disease. Satdarshan (Paul) Singh Monga, MD is Director: Division of Experimental Pathology and Associate Professor of Pathology and Medicine, University of Pittsburgh, Pittsburgh, PA
Molecular Basis of Hepatic Physiology -- Gross and Cellular Anatomy of the Liver -- Liver Zonation -- Hepatocytes -- Biliary Epithelial Cells -- Stellate Cells -- Kupffer Cells -- Sinusoidal Endothelial Cells -- Carbohydrate Metabolic Functions of the Liver -- Protein Metabolic Functions of the Liver -- Fat Metabolic Functions of the Liver -- Detoxification Functions of the Liver -- Synthetic Functions of the Liver -- Bilirubin Metabolism -- Bile Acid Metabolism -- Liver Development -- Transcriptional Control of Hepatic Differentiation -- Liver Regeneration -- Liver Stem Cells -- Apoptosis and Necrosis -- Hepatic Fibrosis and Cirrhosis -- Ischemia-reperfusion Injury -- Fatty Liver -- Cholestasis -- Portal Hypertension -- Inflammation -- Oxidative Stress -- NAFLD -- ALD -- Viral Hepatitis -- Autoimmune Hepatitis -- Toxic Liver Injury -- Wilson's Disease -- Hemochromatosis -- Glycogen Storage Diseases -- al-Antitrypsin Deficiency -- Hepatic Artery Obstruction -- Portal Vein Obstruction -- Hepatic Vein Thrombosis -- Primary Biliary Cirrhosis -- Primary Sclerosing Cholangitis -- Benign Hepatic Tumors -- Benign Biliary Tumors -- Experimental Carcinogenesis -- Cancer Stem Cells -- Primary Hepatocellular Carcinoma -- Fibrolamellar Variant of HCC -- Metastatic Diseases to the Liver -- Cholangiocarcinoma -- Molecular Pathology of Extrahepatic Bile Ducts and Gall Bladder -- Developmental Disorders of the Extrahepatic Bile Duct -- Choledocholithiasis, Cholangitis, Gallstones -- and Cholecystitis -- Carcinoma of Extrahepatic Bile Duct -- Gall Bladder Neoplasms -- Index.
Keywords: Medicine; Pathology; Medicine & Public Health; Pathology; Molecular Medicine